PERAN MODAL SOSIAL TERHADAP KEBERDAYAAN PETANI KARET DI DESA KUNTU KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Apriansah, Agus '; Sayamar, Eri '; Yulida, Roza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims: identified social capital rubber farmers, identified the role of social capital on rubber farmers empowerment, identified the relationship between social capital and the role of social capital on rubber farmers empowerment. This research uses a purposive sampling method with respondents consist of 60 rubber farmers in Desa Kuntu. Data collection method in this research is primary data and secondary data. To determine the social capital and the role of social capital in this research using a quantitative method use a questionnaire in the form of Likert Scale. To analyze the relationship of social capital and the role of social capital uses Spearman rank correlation analysis. From the research data showed that social capital rubber farmers is high with a score 3.94 and the role of social capital to empowerment of farmers is high with a score 3.95. Based on the statistic results using Spearman's test can be showed that overall there is a strong enough relationship between the variables of the role of social capital with elements of social capital with a probability value (p < 0.05). Keywords: Empowerment of Farmers, Social Capital, the Role of Social Capital